Successful endovascular repair of a giant pseudoaneurysm of the innominate artery with a covered stent - Mera, Pedro A.; Cid, Mariel R.; Almonte, Ravel (International Surgery Journal, 2025)
Pseudoaneurysm of the branches of the aortic arch resulting from blunt thoracic trauma is rare; however, when present, it may compromise the integrity of the innominate artery and the aortic isthmus. We present the case of a 54-year-old man with a known history of hypertension and rheumatoid arthritis, who was referred to the head and neck surgery service for consultation, presenting with a pulsatile mass at the base of the anterolateral side of the neck, progressive dysphonia, dysphagia, and progressive weight loss. Computed tomography (CT) angiography of the neck revealed a giant pseudoaneurysm displacing structures of the neck and mediastinum. The patient was eligible for endovascular exclusion of the pseudoaneurysm. The procedure was successfully performed under local anesthesia.